Oviposition pattern and within-season spatial and temporal variation of pre-dispersal seed predation in a population of Mimosa bimucronata trees - Rossi, Marcelo N.; da Silva Rodrigues, Ligia M. [UNESP]; Ishino, Marcos N. [UNESP]; Kestring, Debora [UNESP] (Springer, 2011)
Spatial and temporal variation of pre-dispersal seed predation was investigated in a population of Mimosa bimucronata trees located in the south-east region of Brazil. Three main hypotheses were addressed: (1) that the life stages of the seed predator Acanthoscelides schrankiae are synchronised with the reproductive stages of its host plant; (2) that seed predation levels vary spatially as a result of differences in fruiting phenology synchrony and fruit production among trees; and (3) that predation levels should be affected by the proximity of trees, showing a spatial structure. Also investigated was the oviposition pattern of A. schrankiae among seeds and fruits. Twenty spatially referenced trees were monitored throughout a year to examine tree phenology and egg laying and adult emergence. The bruchine's life stages were synchronised with the reproductive stages of M. bimucronata trees. Egg distribution among seeds and fruits was aggregated. Infestation rates of adult bruchines were not spatially related to fruiting phenology and there is evidence that seed predation is a spatially density-independent process, because the relationship between infestation rates and fruit production was not significant. Finally, it was observed that the distribution of adult bruchines was spatially structured, because similar levels of infestation were found among nearby trees.
Keywords: Bruchinae; Oviposition; Plant phenology; Seed predation; Spatiotemporal variation; Synchrony